PREVALENCE OF SEXUAL VIOLENCE AND RELATIONSHIP BETWEEN ACCUSED AND VICTIM CASES ATTENDED IN ONE STOP CRISIS MANAGEMENT CENTER OF CENTRAL NEPAL - Shrestha, Kaschev; Shah, Dhiraj; Shrestha, Natasha; Prasad Upadhyay, Hari (Journal of Chitwan Medical College, 2024)
Background: Sexual violence is a global public health issue, drawing more concern compared to other forms of violence. Evidence indicates that adolescents face an increased risk of encountering both physical and sexual violence. Despite this, there is a scarcity of nationally representative research on sexual violence in Nepal, hindering the development of informed interventions. This paper seeks to determine the prevalence of sexual violence and relationship between accused and the victim cases attended in one stop crisis management center of central Nepal. Methods: A retrospective cross-sectional study was carried out in the department of Forensic Medicine of College of Medical Sciences in Bharatpur, Chitwan, Nepal, from January, 2023 to January 2024. Ethical approval was taken from institutional review committee of College of Medical Sciences, Bharatpur, Chitwan. Data was entered and analyzed by using descriptive statistical tools in SPSS-16. Results: The prevalence of sexual violence was 41.97% (with 95% CI as 36.31% to 47.62%). Out of 123 sexual violence cases majority (40.65%) of them were in the age group less than 14years followed by 38.21% in the age group 15-18 years. Majority of the victim were female (99.2%) by gender and Janajati (52.8%) by ethnicity. majority (78.9%) were victim of forcefully sexual intercourse. Most of the accused person (20.3%) were stranger followed by boyfriend (17.9%). Conclusions: The prevalence of sexual violence is almost half among all type of violence. Majority of the victim were Adolescence girls and they were from janajati. One out of ten victim had present of body injuries while two out of ten had genital injuries. Most of the accused person were known person (boyfriend, Neighbors, Uncle and cousin). The statistically significant variables were age and gender.